The Kinetic Effects, Caused by Thickness Fluctuations of Quantum Semiconductor Wire - M.A. Ruvinskii; B.M. Ruvinskii; O.B. Kostyuk (Журнал нано- та електронної фізики)
The electrical conductivity, thermopower and thermal conductivity of semiconductor quantum wire conditioned by a random field of Gaussian fluctuations of wire thickness are theoretically determined. We present the results for cases nondegenerate and generate statistics of carriers. The considered mechanism of relaxation of the carriers is essential for sufficiently thin and clean wire from the А3В5 and А4В6 type of semiconductors at low temperatures. The quantum size effects that are typical of quasi-one-dimensional systems were revealed.